SUPERIOR BORDER VERSUS LATERAL BORDER MINIPLATE FIXATION IN MANAGEMENT OF MANDIBULAR ANGLE FRACTURE – A COMPARISON OF TWO TECHNIQUES - Dr. Mohammad Danish; Dr. Syed Sayeed Ahmed; Dr. Gulam Sarwar Hashmi; Dr. Sajjad Abdur Rahman (Medico Research Chronicles, 2018)
Objective: The purpose of this study is to compare the outcome of two surgical approaches i.e. 1.intraoral superior border and 2. transbuccal lateral cortical plating for the management of angle of mandible fracture.Methods: Cohort study conducted during December 2014 to December 2016. Total 20 patients were selected for this study. Patients were equally divided into transbuccal and transoral groups. SPSS Inc was used to compare the outcomes of the two surgical methods.Results: Two patients showed sign of infection in which both showed dehiscence of incision and exposure of miniplates in Superior border fixation group. No patient showed a sign of infection in group 2. More time required for superior border fixation (mean- 63.9000 minutes) as compared to lateral border fixation (mean- 53.100 minutes). Neurosensory disturbance and the postoperative scar were higher in the 2nd group.Conclusion: Transbuccal fixation technique is a superior fixation technique as compared to transoral fixation approach for the treatment of mandibular angle fractures.